LMI-based digital redesign of linear time-invariant systems with state-derivative feedback - Cardim, Rodrigo [UNESP]; Teixeira, Marcelo C. M. [UNESP]; Faria, Flávio A. [UNESP]; Assunção, Edvaldo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
A simple method for designing a digital state-derivative feedback gain and a feedforward gain such that the control law is equivalent to a known and adequate state feedback and feedforward control law of a digital redesigned system is presented. It is assumed that the plant is a linear controllable, time-invariant, Single-Input (SI) or Multiple-Input (MI) system. This procedure allows the use of well-known continuous-time state feedback design methods to directly design discrete-time state-derivative feedback control systems. The state-derivative feedback can be useful, for instance, in the vibration control of mechanical systems, where the main sensors are accelerometers. One example considering the digital redesign with state-derivative feedback of a helicopter illustrates the proposed method. © 2009 IEEE.
Keywords: Control of mechanical systems; Digital redesign; Linear matrix inequalities; State-derivative feedback; Continuous time; Control laws; Discrete-time; Feedforward control law; Feedforward gain; Linear time invariant systems; Multiple inputs; SIMPLE method; State-derivative feedback control; Time invariants; Adaptive control systems; Analog to digital conversion; Continuous time systems; Discrete time control systems; Feedback control; Feedforward control; Flight control systems; Invariance; Mechanics; Mechatronics; State feedback; Switching systems; Time varying control systems; Vibrations (mechanical); Feedback